A characterisation of thermoregulatory responses in elite open water and pool swimming competition - Markey, K.; Galan-Lopez, N.; Esh, C.; Chrismas, B.; Barry, L.; Constantini, N. W.; Adams, W. M.; Mountjoy, M. L.; Taylor, L. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Elite open water swimming (OWS) competitions are conducted in divergent water temperatures (Tw; limits: 16-31°C) thus presenting hypo- and hyper-thermic risk [modest deviations (± 0.5-2°C) in core temperature (Tc) have proven fatal]. Despite OWS specific risk, limited: (i) Tc data in competition-relevant Tw; and (ii) knowledge of real-world and athlete adopted thermoregulatory (Treg) aligned preparations for competition, are seen. In contrast, elite pool-based swimming (PBS) competition exposes swimmers to multiple albeit different (compared to OWS) Treg challenges. PBS competition can span * 8-10h across multiple days (e.g., heats and events) including multiple cycles of warm-ups (WU), priming and cool-downs within and between days/races including an often-prolonged transition phase (TP; >30 minutes) between warm-up end and race start. Thus, attaining and sustaining warm-up derived elevations in Tc until race start can be challenging. Treg-focused strategies in land-based sports are successful and well-evidenced however, such attention is not present in elite swimming. METHODS: Tc was characterised for 25 (9 females, 19.4 ± 2.7 y) elite, national, European, or World/Olympic pool (n=6) and open water swimmers (n=19) using ingestible thermometry. In-race data was collected at the 2023 LEN European Swimming Championships, Leg 4 of the LEN Open Water Cup (18.2°C, COLD event), and the LEN Jnr European OWS Championships (25.5°C, WARM event). Tc in OWS and fluctuations during PBS WU and TP were calculated. Tc change (delta/min) was determined within time period (WU, TP) for PBS and relative to race start for OWS. A preparation and competition aligned knowledge survey was completed within COLD/WARM, including heat acclimation/acclimatisation (HA) preparation use. RESULTS: Divergent Tc responses [mean (min-max); mean */min] were evident (COLD: 37.6°C, 35.0-39.0°C, */min -.001°C; WARM: 38.2°C, 35.8-39.5°C, */min .003°C). 22% (WARM) used HA pre-competition. Of those who adopted HA in WARM, 11% suffered from negative symptomology related to Tc in-race, compared to 33% who did not HA. Tc increased pre to post PBS WU (37.8°C, 36.7 - 38.7°C, */min .009°C). However, 90% of swimmers saw a reduced Tc (37.8°C, 36.7-38.7°C, */min -.108°C) across TP, from WU end to race start. 3/6 PBS swimmers had a pre-race (mean ± SD; 37.4 ± 0.3°C) Tc lower than that at warm-up onset (37.6 ± 0.3°C; */min -.002°C). CONCLUSION: Divergent Tc responses were evident within COLD/WARM. HA appears to offer some protection against undesired body temperature related symptomology in OWS. Therefore, individualised Treg competition practises would be favourable to protect athlete health and optimise performance in OWS. PBS WU derived increases in Tc have generally dissipated by race start due to practices adopted in TP (3/6 swimmers had a lower Tc at race start compared to WU onset). Increasing Tc further during PBS WU and adopting passive heat maintenance strategies (e.g., insulative/heated clothing) would be prudent.